2020
DOI: 10.1007/s10147-020-01652-7
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of involved field radiotherapy and elective nodal irradiation in combination with concurrent chemotherapy for T1bN0M0 esophageal cancer

Abstract: BackgroundThe optimal radiation field of chemoradiation therapy (CRT) for stage I esophageal squamous cell carcinoma (ESCC) is unknown. This retrospective study compared efficacy and safety of two CRT modalities, involved field irradiation (IFI) and elective nodal irradiation (ENI), when treating patients with clinical stage I (T1bN0M0) ESCC. MethodsPatients had received 60 Gy CRT concurrently with 5-FU and cisplatin between January 2000 and December 2012. The clinical target volume of IFI was limited to the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 19 publications
0
13
0
Order By: Relevance
“…No significant differences were observed, although obvious heterogeneities were found among these studies (P < 0.00001; I 2 , 71%). As studies by Nakatani et al (24), Q. F. Li et al (26), and Zhu et al ( 22) contributed significantly and weighted similarly, we excluded these three studies and found that the 3-year OS rates remained unchanged (pooled RR, 0.93; 95% CI, 0.85-1.02; P = 0.15; moderate certainty), with no significant heterogeneity (P = 0.15; I 2 , 31%; Figure 2C). With regard to subgroup, the study type (Supplementary Figure 9A for RCTs group, and Supplementary Figure 9B for non-RCTs group), the type of radiotherapy (Supplementary Figure 10A for the 3D- CRT group, Supplementary Figure 10B for IMRT group, and Supplementary Figure 10C for 3D-IMRT-mixed group), the type of pathology (Supplementary Figure 11A for the ESCC group, and Supplementary Figure 11B for ESCC-mixed group), and the type of chemotherapy received (Supplementary Figure 12A for the CCRT group, Supplementary Figure 12B for CCRT+CT group, and Supplementary Figure 12C for CRTmixed group), there were no substantial differences between them.…”
Section: Os Ratesmentioning
confidence: 79%
See 3 more Smart Citations
“…No significant differences were observed, although obvious heterogeneities were found among these studies (P < 0.00001; I 2 , 71%). As studies by Nakatani et al (24), Q. F. Li et al (26), and Zhu et al ( 22) contributed significantly and weighted similarly, we excluded these three studies and found that the 3-year OS rates remained unchanged (pooled RR, 0.93; 95% CI, 0.85-1.02; P = 0.15; moderate certainty), with no significant heterogeneity (P = 0.15; I 2 , 31%; Figure 2C). With regard to subgroup, the study type (Supplementary Figure 9A for RCTs group, and Supplementary Figure 9B for non-RCTs group), the type of radiotherapy (Supplementary Figure 10A for the 3D- CRT group, Supplementary Figure 10B for IMRT group, and Supplementary Figure 10C for 3D-IMRT-mixed group), the type of pathology (Supplementary Figure 11A for the ESCC group, and Supplementary Figure 11B for ESCC-mixed group), and the type of chemotherapy received (Supplementary Figure 12A for the CCRT group, Supplementary Figure 12B for CCRT+CT group, and Supplementary Figure 12C for CRTmixed group), there were no substantial differences between them.…”
Section: Os Ratesmentioning
confidence: 79%
“…No significant differences were observed, although obvious heterogeneities were found among these studies (P < 0.00001; I 2 , 74%). Subsequently, we excluded the study by Nakatani et al (24) and found that the IFI group had a significant advantage over the ENI group in terms of 5year OS rates (pooled RR, 0.78; 95% CI, 0.68-0.90; P = 0.0004; high certainty; Figure 2D), with no significant heterogeneity (P= 0.31; I 2 , 14%). With regard to subgroup, the type of radiotherapy, the IFI group had a significant advantage over the ENI group in the IMRT subgroup (Supplementary Figure 13A), whereas no differences were observed in the 3D-IMRT-mixed subgroup regarding the 5-year OS rate (Supplementary Figure 13B).…”
Section: Os Ratesmentioning
confidence: 99%
See 2 more Smart Citations
“…In the JCOG 9708 study, although 87.5% of patients achieved complete remission, the 4-year recurrence-free survival rate was 52.8%. According to existing studies, overall recurrence rate after radiotherapy (RT) or CRT for stage I ESCC was 20–40%, while the intraesophageal recurrence rate was 10–30% [ 5 9 ].…”
Section: Introductionmentioning
confidence: 99%